Implementación de un módulo didáctico para el control de variables analógicas como: temperatura, desplazamiento y presión mediante el sistema scada telemetría con la utilización de plc (s7-1200) en el laboratorio de automatización de la Universidad Técnica de Cotopaxi en la ciudad de Latacunga en el periodo 2015 - Andrade Sánchez, Galo Andrés (2016)
This project concerns make the realization of a training module, this means that students from the Technical University of Cotopaxi can do internships concerning the variables temperature, displacement and pressure with the help of electronic parts such as PLC, S, sources, touch panel screens, etc. With this module, students will do internships in real-time industrial processes with the help of computer programs. Whether the training module will also indicate the forms of connection required for operation will also be able to see the different devices required in the assembly module explained above. Students of different races of Engineering can do internships with no problem because the module is very easy to use and well in every race engineering is a priority the use of electronic systems and professional level that is very common to find this type of control systems for different processes. Whether students will always fully open to the use of the project helping their theoretical knowledge and especially practical skills.